An evolutionary perspective on the resistance of Daphnia to the epizoic rotifer Brachionus rubens. (24th February 2014) - Pauwels, Kevin; De Meester, Luc; Michels, Helen; Jeppesen, Erik; Decaestecker, Ellen
Summary In considering the evolutionary dynamics of host–parasite interactions, it is usually assumed that host populations are able to evolve rapidly under selection from various parasitic pressures. This has been shown for endoparasites, but for ectoparasites and/or epibionts, in general, less strong effects are expected on their hosts. We show that the exposure of Daphnia magna clones (of a different origin) to lake sediment from the Danish Lake Ring, containing dormant eggs of the epizoic rotifer Brachionus rubens, results in infections that are associated with increased mortality in Daphnia. Using a resurrection ecology approach, we reconstructed evolutionary change in the Lake Ring D. magna population in response to B. rubens infections. We observed interclonal variation in resistance to B. rubens in this Daphnia population, as well as changes over time in resistance to rotifers. Both sediment exposure and time period from which Lake Ring clones were isolated affected important life‐history parameters, suggesting that evolution (upon exposure to Brachionus) not only affected resistance to Brachionus, but also other traits in Lake Ring Daphnia. Additionally, there were complex effects of a joint exposure of D. magna to rotifers and the indirect effect of fish predation: exposure to fish kairomones resulted in an increased allocation of energy to early reproduction and Daphnia performance. Further, fish kairomones apparently increased B. rubens infectivity.